2023
DOI: 10.2147/idr.s396570
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Carriage Rate of Staphylococcus aureus, Its Associated Factors, and Antimicrobial Susceptibility Pattern Among Health Care Workers in Public Hospitals, Harar, Eastern Ethiopia

Wondimagegn Wolde,
Habtamu Mitiku,
Rajesh Sarkar
et al.

Abstract: Background Staphylococcus aureus is the bacteria that colonizes the nasal nares of health-care workers and serves as a reservoir for the spread of pathogen for subsequent infections, mainly Methicillin-resistant Staphylococcus aureus . However, there is a limited study conducted regarding this topic in Harar, Eastern Ethiopia. Objective The main objective of this study was to determine the prevalence of nasal carriage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
2
0
0
Order By: Relevance
“…In addition, highest colonization rate of MRSA 3(60%) were observed among nurses and doctors 1(50%) followed by midwifes 2(28.6%). Which is coincides with similar study conducted in Harar, Eastern Ethiopia where nursing and doctors carriage of MRSA were reported 15.3%, 11.1% respectively (32). GAZA strip, where nursing and doctors carriage of MRSA were also observed (30.4%) and (16%) respectively (34).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, highest colonization rate of MRSA 3(60%) were observed among nurses and doctors 1(50%) followed by midwifes 2(28.6%). Which is coincides with similar study conducted in Harar, Eastern Ethiopia where nursing and doctors carriage of MRSA were reported 15.3%, 11.1% respectively (32). GAZA strip, where nursing and doctors carriage of MRSA were also observed (30.4%) and (16%) respectively (34).…”
Section: Discussionsupporting
confidence: 90%
“…The present study showed that there was no signi cant association between carriage of MRSA with sex (p = 0.085), Age (p = 0.503), history of hypertension (p = 0.241), history of diabetics (p = 0.124), recent use of antibiotics (p = 0.682), profession (p = 0.440).But it is, however length of healthcare services (p = 0.033) was highly signi cant associated with colonization rate of MRSA which is comparable with similar study done in Ethiopia (32). Furthermore, relatively high carriage rate of MRSA colonization were observed among the males than females in the current study which is in agreement with those reported in Saudi Arabia (35).…”
Section: Discussionsupporting
confidence: 72%